Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 41555 by Raj Singh last updated on 09/Aug/18

Answered by alex041103 last updated on 09/Aug/18

1. ∫((ln x)/((1+ln x)^2 )) dx  let x=e^u  dx=e^u du.  ∫((1+u−1)/((1+u)^2 ))e^u du=∫(e^u /(1+u))du−∫(e^u /((1+u)^2 ))du=  =∫(e^u /(1+u))du+∫e^u d((1/(1+u)))= now by parts  =∫(e^u /(1+u))du+(e^u /(1+u))−∫(e^u /(1+u))du=(e^u /(1+u))  ⇒∫((ln x)/((1+ln x)^2 )) dx=(x/(1+ln x))+C

1.lnx(1+lnx)2dxletx=eudx=eudu.1+u1(1+u)2eudu=eu1+udueu(1+u)2du==eu1+udu+eud(11+u)=nowbyparts=eu1+udu+eu1+ueu1+udu=eu1+ulnx(1+lnx)2dx=x1+lnx+C

Answered by tanmay.chaudhury50@gmail.com last updated on 09/Aug/18

1)∫((1+lnx−1)/((1+lnx)^2 ))dx  ∫(((1+lnx)(dx/dx)−x.(d/dx)(1+lnx))/((1+lnx)^2 ))dx  ∫(d/dx)((x/(1+lnx)))dx  ∫d((x/(1+lnx)))  (x/(1+lnx))+c

1)1+lnx1(1+lnx)2dx(1+lnx)dxdxx.ddx(1+lnx)(1+lnx)2dxddx(x1+lnx)dxd(x1+lnx)x1+lnx+c

Answered by alex041103 last updated on 09/Aug/18

2. ∫((sin(ln x))/x^3 )dx  First way: simply integrate  x=e^u  dx=e^u du  ∫((sin(ln x))/x^3 )dx=∫((sin(u))/e^(3u) )e^u du=  =∫e^(−2u) sin(u)du=I  IBP (1)  I=−(1/2)e^(−2u) sin(u)+(1/2)∫e^(−2u) cos(u)du  IBP (2)  I=−(1/2)e^(−2u) sin(u)+(1/2)(−(1/2)e^(−2u) cos(u)−(1/2)∫e^(−2u) sin(u)du)=  =−(1/2)e^(−2u) sin(u)−(1/4)e^(−2u) cos(u)−(1/4)I  ⇒(5/4)I=−(1/2)e^(−2u) sin(u)−(1/4)e^(−2u) cos(u)  ⇒∫e^(−2u) sin(u)du=−(2/5)e^(−2u) sin(u)−(1/5)e^(−2u) cos(u)  ∫e^(−2u) sin(u)du=−(1/5)e^(−2u) (2sin(u)+cos(u))  ⇒∫((sin(ln x))/x^3 )dx=−(1/(5x^2 ))(2sin(ln x)+cos(ln x))+C

2.sin(lnx)x3dxFirstway:simplyintegratex=eudx=eudusin(lnx)x3dx=sin(u)e3ueudu==e2usin(u)du=IIBP(1)I=12e2usin(u)+12e2ucos(u)duIBP(2)I=12e2usin(u)+12(12e2ucos(u)12e2usin(u)du)==12e2usin(u)14e2ucos(u)14I54I=12e2usin(u)14e2ucos(u)e2usin(u)du=25e2usin(u)15e2ucos(u)e2usin(u)du=15e2u(2sin(u)+cos(u))sin(lnx)x3dx=15x2(2sin(lnx)+cos(lnx))+C

Commented by alex041103 last updated on 09/Aug/18

Second way: Complex Analysis  sin(ln x)=Im(e^(i ln x) )=Im(x^i )  ⇒∫((sin(ln x))/x^3 )dx=Im(∫x^(i−3) dx)=  =Im((x^(i−2) /(i−2)) ((−i−2)/(−i−2)))=−(1/(5x^2 ))Im((2+i)x^i )=  =−(1/(5x^2 ))Im((2+i)(cos(ln x)+isin(ln x)))=  =−(1/(5x^2 ))(2sin(ln x)+cos(ln x))  ⇒∫((sin(ln x))/x^3 )dx=−(1/(5x^2 ))(2sin(ln x)+cos(ln x))+C

Secondway:ComplexAnalysissin(lnx)=Im(eilnx)=Im(xi)sin(lnx)x3dx=Im(xi3dx)==Im(xi2i2i2i2)=15x2Im((2+i)xi)==15x2Im((2+i)(cos(lnx)+isin(lnx)))==15x2(2sin(lnx)+cos(lnx))sin(lnx)x3dx=15x2(2sin(lnx)+cos(lnx))+C

Answered by tanmay.chaudhury50@gmail.com last updated on 09/Aug/18

2)∫((sin(lnx))/x^3 )dx  t=lnx   dt=(dx/x)    [and x=e^t   ∫((sint)/e^(2t) )dt  ∫e^(−2t) sint dt  p=∫e^(−2t) cost dt  q=∫e^(−2t) sint dt  p+iq=∫e^(−2t) .e^(it) dt  p+iq=∫e^(t(−2+i)) dt  =(e^(t(−2+i)) /(−2+i))+c  =((e^(−2t) .e^(it) )/((−2+i)(−2−i)))×(−2−i)+c  =e^(−2t) .(((cost+isint))/(4+1))×(−2−i)+c  =(e^(−2t) /5)(cost+isint)(−2−i)+c  =(e^(−2t) /5)(−2cost−icost−i2sint+sint)+c  =(e^(−2t) /5){(−2cost+sint)+i(−cost−2sint)}+c  real part  =(e^(−2t) /5)(−2cost+sint)+i(e^(−2t) /5)(−cost−2sint)+c  ∫e^(−2t) sint dt  =(e^(−2t) /5)(−cost−2sint)+c  =(x^(−2) /5){−cos(lnx)−2sin(lnx)}+c

2)sin(lnx)x3dxt=lnxdt=dxx[andx=etsinte2tdte2tsintdtp=e2tcostdtq=e2tsintdtp+iq=e2t.eitdtp+iq=et(2+i)dt=et(2+i)2+i+c=e2t.eit(2+i)(2i)×(2i)+c=e2t.(cost+isint)4+1×(2i)+c=e2t5(cost+isint)(2i)+c=e2t5(2costicosti2sint+sint)+c=e2t5{(2cost+sint)+i(cost2sint)}+crealpart=e2t5(2cost+sint)+ie2t5(cost2sint)+ce2tsintdt=e2t5(cost2sint)+c=x25{cos(lnx)2sin(lnx)}+c

Answered by maxmathsup by imad last updated on 09/Aug/18

let I = ∫  ((sin(ln(x)))/x^3 ) dx  chamgement  ln(x) =t give  I =  ∫     ((sin(t))/e^(3t) ) e^t dt  =∫   e^(−2t)  sint dt  = Im(  ∫  e^(−2t +it) dt) but  ∫  e^((−2+i)t) dt = (1/(−2+i)) e^((−2+i)t)  +c =−((2+i)/5) e^(−2t)  (cost +isnt) +c  =−(1/5) e^(−2t) { 2cost +2isint  +icost −sint}+c  =−(1/5) e^(−2t) {2cost −sint +i(2sint +cost)} ⇒  I =−(e^(−2t) /5){ 2sin(t)+cos(t)} +k

letI=sin(ln(x))x3dxchamgementln(x)=tgiveI=sin(t)e3tetdt=e2tsintdt=Im(e2t+itdt)bute(2+i)tdt=12+ie(2+i)t+c=2+i5e2t(cost+isnt)+c=15e2t{2cost+2isint+icostsint}+c=15e2t{2costsint+i(2sint+cost)}I=e2t5{2sin(t)+cos(t)}+k

Commented by maxmathsup by imad last updated on 09/Aug/18

but t =ln(x) ⇒ I =−(1/(5x^2 )){ 2sin(ln(x)) +cos(ln(x))} +k

butt=ln(x)I=15x2{2sin(ln(x))+cos(ln(x))}+k

Terms of Service

Privacy Policy

Contact: info@tinkutara.com